2014
DOI: 10.1177/0004563214526169
|View full text |Cite
|
Sign up to set email alerts
|

Regan isoenzyme of alkaline phosphatase as a tumour marker for renal cell carcinoma

Abstract: Alkaline phosphatase is an enzyme present in all tissues of the human body. Several isoforms of this enzyme have been described with different catalytic nature, stability and antigenic structure. Rises in the activity of alkaline phosphatase are recognised in various states including bone diseases, liver disease, pregnancy, hyperthyroidism and malignant processes. The Regan isoenzyme, a rare variant of placental alkaline phosphatase, has been identified circulating in association with various tumours. The repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Since 5-ALA-induced PpIX is selective for tumors, we hypothesized that the introduction of an N-terminal group that can be activated by ubiquitously expressed enzymes would circumvent this problem. Therefore, we have focused our efforts on the design and synthesis of novel classes of 5-ALA derivatives modified at the amino group that can be activated in vivo by alkaline phosphatases [35], ubiquitous enzymes present in all tissues and known to be overexpressed in certain types of tumors [36][37][38][39]. To the best of our knowledge this is the first time that the 5-amino group has been successfully protected using a phosphate group.…”
Section: Introductionmentioning
confidence: 99%
“…Since 5-ALA-induced PpIX is selective for tumors, we hypothesized that the introduction of an N-terminal group that can be activated by ubiquitously expressed enzymes would circumvent this problem. Therefore, we have focused our efforts on the design and synthesis of novel classes of 5-ALA derivatives modified at the amino group that can be activated in vivo by alkaline phosphatases [35], ubiquitous enzymes present in all tissues and known to be overexpressed in certain types of tumors [36][37][38][39]. To the best of our knowledge this is the first time that the 5-amino group has been successfully protected using a phosphate group.…”
Section: Introductionmentioning
confidence: 99%
“…Fishman (1980) contends that PLAP is sometimes found in individuals with ulcerative colitis or polyposis of the colon, and it is through this that they enhance the capability of acquiring cancer [17]. Bukowczan et al also examined that PLAP has a relationship with different tumors such as renal cell carcinoma (RCC) [18].…”
Section: Alp Isoenzyme and Testsmentioning
confidence: 99%
“…Studies have shown that the increase of Regan isoenzyme of alkaline phosphatase is closely related to the occurrence of occult renal cell carcinoma. The continuous increase after operation indicates the persistence or recurrence of the disease 2 . Leucine aminopeptidase (LAP) is also an important marker for cancer diagnosis as it is overexpressed in many cancers.…”
Section: Introductionmentioning
confidence: 99%